Oxidation of azo dye Orange II with hydrogen peroxide catalyzed by 5,10,15,20-tetrakis[4-(diethylmethylammonio)phenyl]porphyrinato-cobalt(II)tetraiodide in aqueous solution - S.H. El-Khalafy; M.T. Hassanein; M.F. Abd-Elal; A.A. Atia (Journal of Saudi Chemical Society)
The catalytic oxidation of the azo dye Orange II by hydrogen peroxide in aqueous solution has been investigated using 5,10,15,20-tetrakis-[4-(diethylmethylammonio)phenyl]porphyrinato-cobalt(II) tetra iodide 1as catalyst. The oxidation reaction was followed by recording the UV–vis spectra of the reaction mixture with time at λmax = 485 nm. The factors that may influence the oxidation of Orange II, such as the effect of reaction temperature, concentration of catalyst, hydrogen peroxide and orange II have been studied. The results of total organic carbon analysis showed 52% of dye mineralization under mild reaction conditions. Residual organic compounds in the reaction mixture were identified by using Gas chromatography-mass spectrometry. The decolorization rate and mineralization of the dye has been found to increase with increase of catalyst concentration and reaction temperature. The rate of dye oxidation decreased with increasing the concentration of dye, H2O2 and at higher pH than 9. Radical scavenging measurement indicated that decolorization of Orange II by H2O2/cobalt (II) porphyrin complex 1 involved the formation of hydroxyl radicals as the active species.